2006
DOI: 10.1042/bj20060259
|View full text |Cite
|
Sign up to set email alerts
|

Gangliosides play an important role in the organization of CD82-enriched microdomains

Abstract: Four-transmembrane-domain proteins of the tetraspanin superfamily are the organizers of specific microdomains at the membrane [TERMs (tetraspanin-enriched microdomains)] that incorporate various transmembrane receptors and modulate their activities. The structural aspects of the organization of TERM are poorly understood. In the present study, we investigated the role of gangliosides in the assembly and stability of TERM. We demonstrated that inhibition of the glycosphingolipid biosynthetic pathway with specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 44 publications
2
75
0
Order By: Relevance
“…16 Tetraspanins are also known to form a specific kind of membrane domains, 46 interact with GSL 18,47 and modulate EGFR signaling. 48 Therefore, TI-VAMPdependent regulation of EGFR may result from its role in transport of components of membrane domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Tetraspanins are also known to form a specific kind of membrane domains, 46 interact with GSL 18,47 and modulate EGFR signaling. 48 Therefore, TI-VAMPdependent regulation of EGFR may result from its role in transport of components of membrane domains.…”
Section: Discussionmentioning
confidence: 99%
“…15 More recently, we showed that VAMP7 mediates transport from the Golgi apparatus to the plasma membrane (PM) particularly of tetraspanins 16 which participate in membrane organization 17 and interact with glycosphingolipids. 18 In addition, VAMP7 is involved in the transport of GLUT1 and Lat, two other membrane domain associated proteins. 19,20 Altogether, these findings led us to hypothesize a more direct contribution of VAMP7 in membrane organization and membrane domains homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Metastasis suppressor tetraspanin CD82/KAI1 has been implicated in the modulation of activities of various transmembrane receptors such as EGFR, c-Met, and ␤1 integrins (5)(6)(7)(8)(9)(10)(11). Specifically, we have previously shown that elevated expression of CD82 in epithelial cells results in the increased internalization rate of EGFR, thus attenuating the signaling of the receptor (5).…”
Section: Ligand-induced Ubiquitylation Of Egf Receptor (Egfr)mentioning
confidence: 99%
“…The latter is not expressed in humans (30). The association of CD82 and other tetraspanins with gangliosides is known to modulate cellular signaling (59,60). Whether CD82 on human neutrophils interacts directly with the sialic acid-containing structures on the porcine endothelium remains to be answered.…”
Section: Discussionmentioning
confidence: 99%